Rio de Janeiro residents’ perceptions of the 2016 Olympics in the pre-games period - Deborah Moraes Zouain; Paola Lohmann; Kaarina Virkki; Douglas Michele Turco; Gabriela De Laurentis Cardoso (Tourism & Management Studies)
Between 2014 and 2016, Rio de Janeiro hosted two mega sport events – the Fédération Internationale de Football Association World Cup and the Olympic Games – which generated changes in the city. This study sought to analyse Rio residents’ perceptions in the lead-up to the latter games. A quantitative survey was conducted face-to-face with a sample of 404 residents, exactly one year before the Olympics. The data indicated that the residents found the pre-game period troubling because of uncertainties regarding the city’s desired Olympic legacy. Residents’ routines were impacted by either traffic issues or media reports that generated expectations and apprehension. The preOlympic period was marked by protests, concerns about overspending, construction delays and fears about the mega-events’ success. However, residents’ perceptions included clear expectations regarding the event legacy’s implications for tourism businesses and the destination’s visibility, as well as lasting improvements affecting tourism and sport activities